IGF1R and MAPK15 Emerge as Potential Targets of Pentabromobenzylisothioureas in Lung Neuroendocrine Neoplasms - Ewelina Motylewska; Marcin Braun; Zygmunt Kazimierczuk; Hanna Ławnicka; Henryk Stępień (MDPI AG, 2020)
Pentabromobenzylisothioureas are antitumor agents with diverse properties, including the inhibition of MAPK15, IGF1R and PKD1 kinases. Their dysregulation has been implicated in the pathogenesis of several cancers, including bronchopulmonary neuroendocrine neoplasms (BP-NEN). The present study assesses the antitumor potential of ZKKs, a series of pentabromobenzylisothioureas, on the growth of the lung carcinoid H727 cell line. It also evaluates the expression of MAPK15, IGF1R and PKD1 kinases in different BP-NENs. The viability of the H727 cell line was assessed by colorimetric MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide) and its proliferation by BrdU (5-bromo-2'-deoxyuridine) assay. Tissue kinase expression was measured using TaqMan-based RT-PCR and immunohistochemistry. ZKKs (10−4 to 10−5 M) strongly inhibited H727 cell viability and proliferation and their antineoplastic effects correlated with their concentrations (p < 0.001). IGF1R and MAPK15 were expressed at high levels in all subtypes of BP-NENs. In addition, the SCLC (small cell lung carcinoma) patients demonstrated higher mRNA levels of IGF1R (p = 0.010) and MAPK15 (p = 0.040) than the other BP-NEN groups. BP-NENs were characterized by low PKD1 expression, and lung neuroendocrine cancers demonstrated lower PKD1 mRNA levels than carcinoids (p = 0.003). ZKKs may suppress BP-NEN growth by inhibiting protein kinase activity. Our results suggest also a possible link between high IGF1R and MAPK15 expression and the aggressive phenotype of BP-NEN tumors.